How to be a brilliant English teacher - Wright, Trevor, 1950- (Milton Park, Abingdon, Oxon : Routledge, 2012)
'Now in its second edition, Trevor Wright's hugely popular How to be a Brilliant English Teacher is packed with practical advice drawn from his extensive and successful experience as an English teacher, examiner and teacher trainer. This accessible and readable guide offers combine sound theoretical principles with exciting practical suggestions for the classroom. Fully updated to include a new chapter on differentiation and inclusion and expanded sections on behaviour management and teaching poetry for enjoyment and personal response, this book tackles other tricky areas such as: - Starting with Shakespeare - Effective planning and assessment - Learning to love objectives - Working small texts and big texts - Drama. Trainee teachers will find support and inspiration in this book and practising English teachers can use it as an empowering self-help guide for improving their skills. Trevor Wright addresses many of the anxieties that English teachers face, offering focused and realistic solutions'--
Includes index.
Keywords: English language -- Study and teaching (Secondary).; English teachers; High school teaching; Effective teaching